Aetiology of Fever of Unknown Origin: One-Year Experience in a Tertiary Care Hospital of Bangladesh (BIRDEM Medical Journal, 2016)
Background: Fever of unknown origin (FUO) is not an uncommon problem in general medical practice. Sometimes extensive investigations fail to reach an aetiological diagnosis; on the other hand, in few cases, fever resolves spontaneously. This study was aimed to evaluate the aetiology of FUO in a tertiary care setting.Methods: This cross-sectional study was done in the Department of Internal Medicine of BIRDEM General Hospital, Dhaka, Bangladesh from July 2012 to June 2013.Results: Among the 33 patients studied (1.23% of total admissions), 22 (66.7%) were male. Mean age of the study population was 40.2±7.9 years. Most patients (84.8%) were diabetic. Infection (20, 60.6%) was the commonest cause, followed by malignancy (9, 27.3%). Among the infective causes (20), extra-pulmonary tuberculosis (5, 25%) was the commonest, followed by liver abscess (4, 20%). Other less common causes were Kala-azar (1), malaria (2), histoplasmosis (2), melioidosis (1), cholecystitis (1), renal abscess (1), rickettsial fever (1), apical dental abscess (1) and infective endocarditis (1). Non-Hodgkins lymphoma (6), renal cell carcinoma (2) and hepatocellular carcinoma (1) constituted the malignant causes of FUO in this series. Systemic lupus erythematosus was the aetiology of FUO in 1 case. One case remained undiagnosed and 2 patients left hospital before a definite diagnosis could be made.Conclusion: Extra-pulmonary tuberculosis and non-Hodgkins lymphoma were the two most common causes of FUO in this study. Repeated history taking, clinical examinations and careful stepwise investigations can diagnose the aetiolgy in most cases of FUO.Birdem Med J 2016; 6(1): 7-11